2020
DOI: 10.2967/jnumed.119.234971
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Distribution of Gastrin-Releasing Peptide Receptors in Cancer

Abstract: Targeting tumor-expressed receptors using selective molecules for diagnostic, therapeutic, or both diagnostic and therapeutic (theragnostic) purposes is a promising approach in oncologic applications. Such approaches have increased significantly over the past decade. Peptides such as gastrin-releasing peptide receptors targeting radiopharmaceuticals are small molecules with fast blood clearance and urinary excretion. They demonstrate good tissue diffusion, low immunogenicity, and highly selective binding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 80 publications
0
49
0
1
Order By: Relevance
“…AF750-6Ahx-Sta-BBN is a GRPR antagonist peptide analog. Siyuan Cheng et al 34 compared GRPR agonist BBN (7)(8)(9)(10)(11)(12)(13)(14) and GRPR antagonist RM26 for prostate cancer PET imaging and found that GRPR antagonist is a candidate for clinical transformation. This present study is the first study to demonstrate the potential of using a GRPR antagonist AF750-6Ahx-Sta-BBN as a potential near-infrared fluorescence imaging probe for OSCC detection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…AF750-6Ahx-Sta-BBN is a GRPR antagonist peptide analog. Siyuan Cheng et al 34 compared GRPR agonist BBN (7)(8)(9)(10)(11)(12)(13)(14) and GRPR antagonist RM26 for prostate cancer PET imaging and found that GRPR antagonist is a candidate for clinical transformation. This present study is the first study to demonstrate the potential of using a GRPR antagonist AF750-6Ahx-Sta-BBN as a potential near-infrared fluorescence imaging probe for OSCC detection.…”
Section: Discussionmentioning
confidence: 99%
“…NaHCO 3 , DMF and other regular reagents were purchased from Sigma-Aldrich (St. Louis, MO, USA). Full length bombesin [1][2][3][4][5][6][7][8][9][10][11][12][13][14] from American Peptide Company (Sunnyvale, CA, USA) was used as the blocking agent in this study. AF750- www.nature.com/scientificreports/ 6Ahx-Sta-BBN was synthesized and purified at the Biomolecular Imaging Center, Harry S. Truman Memorial Veterans' Hospital, and University of Missouri, Columbia, Missouri, United States, according to our published procedure 27 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations